Forandrer Facebook partiernes forhold til vælgerne? - Højholt, Lars Duvander; Kosiara-Pedersen, Karina (Politik, 2011)
To what extent have Danish parties and party leadership created new relationship with the electorate by applying relationship marketing via Facebook? Are parties using Facebook? If yes, what characterizes the interaction between party leadership and electorate on Facebook? Danish MPs apply Facebook but the ap- plication seems to be more personally than politically motivated. Only a quarter of the MPs have a site that is electorally adequate. All party leaders have sites but their level of activity varies. Interaction takes place but mainly among friends and fans; not including the party leadership. When parties encourage the electorate to ‘follow us on Facebook’ this is the correct wording; it is not an invitation to dialogue. But party leaders may contribute towards political dialogue if they want, as party leaders seeking dialogue get it.